Going to the dentist - Frost, Helen, 1949- (Mankato, Mn. : Pebble Books, 1999)
An introductory look at a dentist's office, including the equipment found there, what the dentist does during a check-up, and cavities.
Includes bibliographical references and index.
13
Keywords: Dentistry; Dentistry -- Juvenile literature; Dental care; Children -- Preparation for dental care -- Juvenile literature